Tren Konsentrasi Uap Air dan Ozon di Beberapa Ketinggian Wilayah Indonesia Akibat Fenomena La Niña - Ariani, Silvi; Vonnisa, Mutya; Marzuki, Marzuki (Jurusan Fisika FMIPA Universitas Andalas, 2024)
We observed the effect of the La Niña phenomenon on the concentration of water vapor and ozone in the Indonesian region. This aims to the value of water vapor and ozone concentrations due to the La Niña phenomenon using Microwave Limb Sounder (MLS) data from 2004-2022. The La Niña phenomenon was chosen because during La Niña, the sea surface temperature in Indonesia is warmer than normal, thus increasing the evaporation of sea water which result is an increase in the concentration of water vapor in the atmosphere. Concentration values are observed at altitudes of (25.7;30.5;35.3;40.1) km because there are trends in water vapor and ozone concentrations at these altitudes. The La Niña phenomenon is used to see anomalies in water vapor and ozone concentrations from their normal state. La Niña phenomenon is observed based on the ONI index. We found that during La Niña, the water vapor concentration increased from its normal state while the ozone concentration decreased from its normal state. These two concentration values were used to find trends using Mann Kendall and Sen's Slope methods. We found that the trend of water vapor concentration is statistically significant while the trend of ozone concentration is the opposite.